ChemInform Abstract: Furospirostanol and Spirostanol Saponins from the Rhizome of Tupistra chinensis and Their Cytotoxic and Antiinflammatory Activities. Issue 21 (6th May 2016) - Xiang, Limin; Wang, Yihai; Yi, Xiaomin; Feng, Jianying; He, Xiangjiu
Abstract: Nine new saponins are isolated and some of them show potent cytotoxic activities against cancer cell lines and significant inhibition on nitric oxide production.